1974
DOI: 10.1161/01.cir.49.5.790
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic Observations in Prehospital Ventricular Fibrillation and Sudden Cardiac Death

Abstract: SUMMARYIn order to better understand the problem of prehospital sudden cardiac death (SCD) two groups of individuals were studied. One group was monitored by rescue squads during attempted rescue. These subjects were defibrillated from prehospital ventricular fibrillation (VF) and hospitalized if they survived or autopsied if they could not be resuscitated. The second group were SCDs which were witnessed and described by observers. Detailed past histories of both groups were collected, and either clinical or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(52 citation statements)
references
References 60 publications
3
45
1
1
Order By: Relevance
“…1 In our study, the left ventricular ejection fraction was less than 0.40 in 82% of patients with VT and 79% of those with sudden death and failed to discriminate between the two groups, supporting the hypothesis that a lower ejection fraction indicates a larger infarct with a higher probability that an arrhythmogenic area is present.…”
Section: Resultssupporting
confidence: 81%
“…1 In our study, the left ventricular ejection fraction was less than 0.40 in 82% of patients with VT and 79% of those with sudden death and failed to discriminate between the two groups, supporting the hypothesis that a lower ejection fraction indicates a larger infarct with a higher probability that an arrhythmogenic area is present.…”
Section: Resultssupporting
confidence: 81%
“…Numerous studies of cardiac arrest victims and survivors of aborted cardiac arrests have identified several potential causes of cardiac arrest, the most common of which is ventricular tachycardia (VT) or fibrillation (VF) due to either acute ischemia or reentry in a healed myocardial scar. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] These studies have focused primarily on the patient with coronary artery disease, including patients with and without heart failure, and may not accurately indicate the frequency of various causes of death in the heart failure population. Heart failure is associated with activation of the sympathetic nervous system and electrolyte abnormalities that could affect arrhythmogenesis.122,24 In addition, heart failure patients are predisposed to systemic and venous thromboemboli that could precipitate cardiac arrest.…”
mentioning
confidence: 99%
“…Autopsy studies among the general population have consistently reported both severe and diffuse coronary artery stenosis among SCD victims. In fact, several studies have reported that >95% of SCD victims had at least 1 coronary artery with ≥75% stenosis, and the majority of victims had multivessel disease, with the prevalence of 3‐ or 4‐vessel disease as high as 60% 19, 24, 25, 26, 27. The lower prevalence of severe stenosis in the current study compared with the aforementioned studies may suggest that the multiple stressors associated with firefighting can trigger a sudden cardiac event in individuals with a lower overall burden of disease.…”
Section: Discussionmentioning
confidence: 99%